An Instructional Design Of Extracurricular Speaking Class At The First Year Of SMPN 2 Kebakkramat In 2014/2015 Academic Year: A Naturalistic Study - Sarlinda, Adisti; , Prof. Dr Endang Fauziati; , Nur Hidayat, M.Pd (2015)
The research is to describe the teaching learning process of speaking skill based on instructional design at SMP Negeri 2 Kebakkramat. The research type is descriptive research.The subject of this research is the English teacher and the students of the first year of SMP N 2 Kebakkramat.The object of the research focuses on an instructional design on extracurriculer speaking class at SMP Negeri 2 Kebakkramat at 2014/2015 academic year. The component of an Instructional Design which includes syllabus, learning objective, classroom procedure, classroom technique, materials and media, teacher's role, learner's role, assessment modal. Data in this research are information about the teaching learning process in the of Field Note and Interview Script.Data sources in this research are event, informant, and document. The writer collects the data by observation, interview, and document analysis. The writer uses the methods for analyzing data such as reduction of the data, conducting display data, and making conclusion or verification. In validity of data, Triangulation is a technique to check the credibility the data of the research. There are four technique of triangulation such as data triangulation or source, investigator triangulation, theoretical triangulation, and methodological triangulation. The results of the research are: 1) The syllabus used by the English teacher for the first year of SMP Negeri 2 Kebak Kramat are three kinds such as lexical syllabus, structural syllabus, and task-based syllabus. 2) The learning objectives in teaching speaking has two kinds, namely general and specific objective. In general learning objective it purposes to develop communicative competence in spoken and written form to deal with the development of science and technology in facing the globalization era. In specific objective, the learning objective of the teaching English is "students can use English to make a simple transactional and interpersonal conversation to interact with their environment". 3)In the classroom procedure in teaching speaking, the teacher uses 5E (Engagement, Exploration, Explanation, Elaboration, Evaluation) and 3E (Engagement, Explanation, Evaluation). 4)The classroom technique used teaching English in Speaking Skill is discussion, problem solving, read aloud, and question/answer. 5) Instructional materials that used in teaching speaking is printed material. It is the textbook the textbook is a taken from textbook English in Focus. Then media used for teaching speaking is the textbook English in Focus and dictionary. 6) The teacher's roles for teaching English in speaking skill are as facilitator, as classroom as instructor, as consultant, and as evaluator. 7) The student's roles for teaching English in speaking skill are as the listener and the performer. 8) The assessment model for teaching English in speaking in SMP Negeri 2 Kebak Kramat is quiz, homework, daily test, and oral test.